Fungal keratitis among inpatients with corneal ulcers in Thai Binh, Vietnam: A retrospective observational study - Nguyen Thi Anh Van; Pham Ngoc Bich; Bui Thi Ngoc Ha; Nguyen Thu Huong (Asian Journal of Medical Sciences, 2024)
Background: Infectious keratitis can be caused by bacteria, fungi, and viruses. Fungi are a common pathogen, especially in developing countries like India, Nepal, and Bangladesh where the prevalence ranges from 20% to 60%. In Vietnam, fungal keratitis accounted for the highest number of keratitis cases in a study conducted at the central eye hospital over a 5-year period (57%). Therefore, it is necessary to collect specific background information connected to the types of fungal keratitis in corneal ulcer cases in this region. Aims and Objectives: The aim of this study was to investigate the prevalence of fungal keratitis and the epidemiological features in 216 cases of fungal keratitis out of a total of 240 cases of infectious keratitis. Materials and Methods: This retrospective study collected secondary data from medical records of 240 inpatients with infectious keratitis who were treated at the ophthalmology hospital in Thai Binh, Vietnam, from January 01st, 2021 to June 30th, 2022. Patients with a positive fungal-directed smear were analyzed in detail for the type of fungus isolated, sociodemographic data, predisposing risk factors, prior treatment modalities, and laboratory results for the distribution pattern of fungus species. Results: Among the 240 cases, 126 (52.5%) were diagnosed with fungal keratitis by direct microscopic examination. Culture results showed the highest rate of Fusarium spp. (43.3%). The age group of 41–60 years was most commonly involved (40.5%). Males were more affected by fungal keratitis than females, (53.2% compared to 46.8%), with farmers being the most common occupation correlated with fungal keratitis (55.6%). The rate of fungal keratitis patients due to agricultural injuries was the highest compared to other risks (47.6%) and most patients self-medicated before going to the hospital, with many not knowing or remembering what medications they had taken (52.4%). Conclusion: The study revealed a high rate of fungal keratitis among the total of infectious keratitis cases in Thai Binh, Vietnam. Fusarium spp. was the most commonly isolated fungi. The study also highlighted the impact of agricultural injuries on fungal keratitis, especially in regions like Thai Binh.